Dinamika Masyarakat Dalam Meningkatkan Efektivitas Penegakan Hukum - Safitri, Intan Dila (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Abstract- This article aims to examine the role of society in improving the effectiveness of law enforcers in Indonesia. This research uses qualitative analysis methods from various sources such as papers, academics, journals and online media. It can be concluded from the discussion that public awareness of the law is still lacking, but the role of the community is also very influential in optimizing the work of law enforcers. Community participation is not only understanding the law, but also obeying, implementing and enforcing existing laws in Indonesia. Public legal awareness greatly influences the success in implementing existing laws. Effective law enforcement has integrity, justice, honesty, commitment, and is guided by applicable laws and regulations..